Different behavior of Nano sheet and Bulk of the hexagonal boron nitride with first principal calculation approach - Abbas FarhadiKoutenaei; Marwa Ali Mahdi; Ali Bahari; Ali Al-Jelif (Progress in Physics of Applied Materials)
In the present work, the electronic, optical, and nano structural properties of boron nitride samples (in monolayer, bilayer and bulk form) were determined with the help of density functional theory (DFT) and calculations using the Siesta package and the generalized gradient approximation (GGA). -PBE) has been discussed. It is found that the bond length, bond angles, and curvature values of boron nitride are almost the same in monolayer, bilayer, and bulk states. Of course, these structures are considered to have planar forms. Considering the existence of the low band gap energy between the bottom of the conduction band and the maximum of the valence band, (although the size of the bandgap decreases with the increase in the number of layers), it can be concluded that the samples are semiconductors.Since there is a relationship between refractive index, magnetic permeability, and electrical permeability (magnetic parameters are not discussed in the present work), dielectric function, reflection coefficient, absorption coefficient, and refractive index are also investigated. The two real and imaginary components of the dielectric function are important in the properties of materials in terms of nanocomposites. Here, special attention is paid to the main peak in the real part of the dielectric constant.